2015
DOI: 10.1007/s11096-015-0094-3
|View full text |Cite
|
Sign up to set email alerts
|

Medication use during end-of-life care in a palliative care centre

Abstract: Background In end-of-life care, symptoms of discomfort are mainly managed by drug therapy, the guidelines for which are mainly based on expert opinions. A few papers have inventoried drug prescriptions in palliative care settings, but none has reported the frequency of use in combination with doses and route of administration. Objective To describe doses and routes of administration of the most frequently used drugs at admission and at day of death. Setting Palliative care centre in the Netherlands. Method In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(89 citation statements)
references
References 43 publications
5
79
2
3
Order By: Relevance
“…Midazolam is often used in terminally ill patients and is the drug of choice for palliative sedation [3][4][5][6]. It is metabolized in a two-phase process.…”
Section: Introductionmentioning
confidence: 99%
“…Midazolam is often used in terminally ill patients and is the drug of choice for palliative sedation [3][4][5][6]. It is metabolized in a two-phase process.…”
Section: Introductionmentioning
confidence: 99%
“…This is a clinically relevant finding given 60 mg was the median dose of midazolam in Masman et al. 's study ().…”
Section: Resultsmentioning
confidence: 69%
“…McNamara, Minton, and Twycross (1991) found that although the median dose was 30-35 mg/24 hrs of midazolam for all indications, the range for muscle relaxation was 10-60 mg/24 hrs, for terminal agitated delirium 10-240 mg/24 hrs and for multifocal myoclonus or as prophylaxis against seizures 15-80 mg/24 hrs. More recently, Masman, van Dijk, Tibboel, Baar, and Mathôt (2015) showed that the median dose had increased to 60 mg/24 hrs since their previous assessment.…”
Section: Final Midazolam Dosementioning
confidence: 99%
“…Elective organization courses for palliative care are crucial to giving viable patient care. Numerous regularly endorsed medications (eg, promethazine, morphine sulfate) might be utilized in nontraditional courses [30]. Topical gels containing metoclopramide, diphenhydramine or lorazepam may found worthful for patients with unmanageable sickness and spewing [31,32].…”
Section: Non-traditional Administration Routesmentioning
confidence: 99%